Budaya Organisasi Dan Dinamika Ruang Redaksi - Hutagalung, Inge (Interaksi: Jurnal Ilmu Komunikasi, 2016)
ABSTRACT This research is a qualitative study with intrepretative paradigm, and it aims to describe and explain about how the organization culture can be also take a part in the process of gatekeping due to the publication process.            The research results indicate that domination value of collectivism culture in media organization tend to lead the policy as well as the gatekeeping process for avoiding confrontation style in seeking and processing the news. In another side, the research results also indicate that domination value of individualism culture tend to lead the gatekeeping process more flexible depend on intuition and feeling of the journalist. Sometimes the journalist using a confrontation style in seeking and processing the news. However, even the media organization tend to have domination value of collectivism or individualism culture, both of them are conduct the process of gatekeeping based on the code of ethic and having an orientation to public sphere as well as their goals that are not only about making money, but also the pursuit of a certain ideal values.  Keywords: value of collectivism, value of individualism, public sphere